“God’s Beloved Sons”: Religion, Attachment, and Children’s Self-Formation in the Slums of Bangkok - Giuseppe Bolotta (Antropologia, 2017)
This article examines the relationship between religion, attachment, and children’s self-formation with regard to children who were born in a slum of Bangkok, and raised as ‘slum children’ (dek salam) in a Catholic NGO, within a primarily Buddhist context. In moving between their home, school, and the NGO, these children are exposed to multiple – and divergent – models of care, which reflect specific religious and socio-political discourses on family, education, ethnicity, and urban poverty in Thailand. The article demonstrates that different forms of adult-child affective relationships represent the political outcome of historically situated relations of power that simultaneously provide dek salam with multiple possibilities of self-formation. While some of these confirm urban poor’s socio-economic and moral subordination, others open up the space for critique and the constitution of a particular kind of political subjectivity in the shadow of the Thai state hegemonic structures.